Identifying dementia as an issue - Ã™Â‚Ã˜Â¨Ã˜Â§Ã˜Â¯Ã›ÂŒ, ÃšÂ©Ã˜Â§Ã™ÂˆÃ™Â‡; Ã˜Â¹Ã™Â„Ã™Â…Ã›ÂŒ, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯ Ã˜Â±Ã˜Â¶Ã˜Â§ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Since the formulation of rulings is directly related to the refinement of issues, the present paper aims at outlining the extent of a mental disorder namely dementia, so that from this perspective an acceptable separation between this and other psychiatric disorders can be achieved in the realm of jurisprudence. Evaluation of narratives, comparing jurisprudential rulings issued in the case of people with mental disorders in various chapters of jurisprudence, and the use of methods such as lexical aggregation and subtraction of meanings, form the basis of achieving that objective. In addition, examining literal and technical meanings, as well as the errors of case-sensitive meanings pertaining to identification of the issue have been perceived as inevitable. The study shows that one of the most important factors involved in the making of ambiguous and ineffective rulings in the case of psychiatric patients is the lack of proper understanding of mental disorders and their definitional boundaries. Therefore, it is suggested that before any investigation and articulation of rulings, every mental disorder should be compared with neighboring concepts; so that in addition to a clear understanding of the subject, the intermingling of titles and the articulation of non-efficient rulings can be avoided. Moreover, by drawing a link between mental disorders in jurisprudence and the ones in psychology, an approximation to the images of the two sciences will be made and the question of efficiency of jurisprudential rulings shall also be considered.